Global Business Process Outsourcing Development and Its Impact Toward Indonesia - Julius Jilbert; Mahlia Muis; Andi Ratna Sari Dewi;; Muhammad Rifai (www.amertainstitute.com, 2023)
This paper is concerned with business process outsourcing (BPO) development growth globally and how Indonesia ranks among the world. BPO is well known theoretically in Indonesia, yet it is practically not embraced or understood by the Indonesian business world. Is this related to the country's socio-economic problem, or do factors such as foreign trade and investment opportunities, economic and financial forces, political and legal forces, and competitive forces play a part? This article then tries to answer the question by elaborating on each factor and putting Indonesia at the cross- sectional diagram in the conclusion to understand where Indonesia stands at the BPO crossroad.